OPTIMALISASI PENGKREDITAN ATAS PAJAK MASUKAN PADA PT PELABUHAN INDONESIA - Sarah Farhatun Nisah (2023)
PT Pelabuhan Indonesia is a company in the field of port services and is under the auspices of a State-Owned Enterprise (BUMN) and has been confirmed as a PKP since 1998. So that the company must carry out its tax obligations with applicable regulations. The problem that may occur is that there is an error in classifying input tax, this is caused by human error when receiving or delivering taxable goods and/or services. As a result, the company cannot know with certainty the amount of input tax that can be credited or expensed. The author has conducted data processing with a descriptive analysis approach, namely describing the case of non-creditable input tax that occurs in the company. In fulfilling the provisions of the latest regulation, namely Law Number 7 of 2021 Article 9 related to input tax crediting, one of the efforts made by the company is optimizing the crediting of input tax. Related to tax management applied by PT Pelabuhan Indonesia is by separating invoices for creditable and non-creditable input tax transactions.